2020
DOI: 10.21037/acs-2020-surd-14
|View full text |Cite
|
Sign up to set email alerts
|

Conduction disorders after aortic valve replacement with rapid-deployment bioprostheses: early occurrence and one-year evolution

Abstract: Background: Rapid-deployment bioprostheses represent one of the newest aortic valve substitutes introduced into clinical practice. The aim of this retrospective single-center study was to evaluate the occurrence of conduction disorders (CDs) after rapid-deployment aortic valve implantation at discharge and at 1-year follow-up, and to identify risk factors for CDs and permanent pacemaker implantation (PPI). Methods: All patients who reached 1-year follow-up after isolated or combined aortic valve replacement (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…The incidence of more than moderate PVL at 5‐years was 0.6% for the Intuity and 1% for the Perceval valve. The incidence of PPI ranged between 4.1% and 8.45% (Supporting Information: Table ) 40–42 . The Intuity valve short‐term mortality ranged between 0.9% and 12.4% while long‐term mortality ranged between 2.6% and 20% (Supporting Information: Table ) 2,43–52 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of more than moderate PVL at 5‐years was 0.6% for the Intuity and 1% for the Perceval valve. The incidence of PPI ranged between 4.1% and 8.45% (Supporting Information: Table ) 40–42 . The Intuity valve short‐term mortality ranged between 0.9% and 12.4% while long‐term mortality ranged between 2.6% and 20% (Supporting Information: Table ) 2,43–52 .…”
Section: Resultsmentioning
confidence: 99%
“…The 6). [40][41][42] The Intuity valve short-term mortality ranged between 0.9% and 12.4% while long-term mortality ranged between 2.6% and 20% (Supporting Information: Table 7). 2,[43][44][45][46][47][48][49][50][51][52] Surgical indications included aortic valve stenosis and mixed valve pathology (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the frequency of LBBB occurrence after surgical AVR, the frequency of new LBBB following AVR seems to be greater than in other studies comparing surgical patients, including the most recently published analysis comprising patients after SURD AVR, in which the frequency reached more than 17% [ 8 ]. In a study carried out by D’Onofrio et al, it was revealed that nearly 40% of patients develop a new conduction disorder after rapid-deployment aortic valve implantation [ 15 ]. Of these, 1/3 recover after 1 year.…”
Section: Discussionmentioning
confidence: 99%